DISCOURSE ANALYSIS: UNCOVERING MEANING AND PRAGMATICS IN TERE LIYENOVELS “PULANG PERGI” - Elyana Feronica Manurung; Rahel Raphita Sinabutar (Adisam Publisher, 2025)
This article delves into the depths of discourse analysis to uncover the nuanced layers of meaning and pragmatics embedded within Tere Liye's novel